ASN Cadre School: A Strategic Breakthrough for Preparing Future ASN Leaders with Integrity and Excellence Towards Indonesia Gold 2045 - Sidqul Anwar, Dadan; Lestari, Ana; Atikasari, Hania; Janata Agasi Al Hilal, Oskar (Iapa Proceedings Conference, 2024)
In order to realize the Indonesia Gold 2045, the Indonesian bureaucracy currently needs cadres of reform leaders. Talents who are prepared to become leaders through a comprehensive competency development process are expected to be able to answer the challenges of the global world and create opportunities for change. This study provides an analysis of the cadre school strategy in preparing ASN leaders with integrity and excellence. The method used is a qualitative method. Data collection techniques using Desk Study (Preliminary Research), Limited Discussion, Focus Group Discussion (FGD), Experts Panel (Seminar or Discussion with Experts), Benchmarking (Field Visit). Informants in this study include consultants and practitioners in the field of human resource management. The results of this study show that in order to prepare high talented ASN future leaders, the cadre school should be developed based on: 1.a high quality recruitment system, 2. A high quality learning system which has a strong foundation in integrity, 3. a guaranteed placement system, and 4. A high collaboration among stakeholders. Cadre schools as a systematic effort to identify potential, leadership competencies and offer fast track careers are expected to be able to create cadres of leaders with high talent and integrity.